Evolution of Canine Parvovirus in Argentina between years 2003 and 2010: CPV2c has become the predominant variant affecting the domestic dog population - Gallo Calderon, Marina Beatriz (2011)
The current frequency of Canine Parvovirus variants (CPV2a, CPV2b and CPV2c) in the Argentine dog population was investigated by PCR amplification of a 583. bp fragment in the VP2 gene. From a total of 79 rectal swab samples that have been submitted to our laboratory since 2008, 55 (69.6%) resulted positive and were further analyzed by direct DNA sequencing. Fifty positives samples (91%) were characterized as CPV2c variant, which appeared in Argentina in the year 2003 and has been the prevalent type since 2008, whereas CPV2a and CPV2b, still found in Argentine dogs, were represented in 3.6% and 5.4% of the population, respectively. Considering that CPV2c is spreading worldwide, and that this variant is also affecting vaccinated dogs, efforts should be made towards the development of new matched CPV vaccines.